THE ROLE OF PARENTAL PRESENCE IN ALLEVIATING ANXIETY IN CHILDREN UNDERGOING ELECTIVE SURGERIES - Dr. Vijayamahantesh S. Kunnur, Dr. P. G. Raghavendra, Dr. Sahana P R (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Preoperative anxiety is a common concern among pediatric patients undergoing surgicalprocedures. Heightened anxiety may lead to difficult anesthesia induction, increased postoperative pain, and longer recovery times